On Foucault and foreign policy: the merits of governmentality for the study of EU external relations. Issue 3 (27th May 2019) - Derous, Marjolein; De Roeck, Frederik
ABSTRACT: This paper demonstrates the merits of governmentality as a tool for studying EU external relations. Existing research tends to fall into the trap of reifying the dichotomy between realist and ideational conceptions of EU external action. Governmentality can serve as a hybrid between these two strands of research, incorporating the preoccupancy with power of the former with the ethical considerations of the latter. It can open up our understanding of power operating in and through the EU's external relations, by looking at the discursive constructions rendering issues governable and the micro-political practices that follow from it. We provide an overview of existing applications of governmentality in EU external relations and construct a framework allowing researchers to use governmentality to its full analytical potential.